Diversification, Size and Risk: the Case of Bank Acquisitions of Nonbank Financial Firms*1. (17th March 2015) - Casu, Barbara; Dontis‐Charitos, Panagiotis; Staikouras, Sotiris; Williams, Jonathan
Abstract: We investigate the risk effects of bank acquisitions of insurance companies and securities firms between 1991 and 2012 using a newly constructed dataset of M&A deals. We examine risk changes before and after deal announcements by decomposing risk into systematic and idiosyncratic components. Subsequently, we investigate the relationship between risk and diversification by modelling the determinants of risks. We find that bank combinations with securities firms yield higher risks than combinations with insurance companies. Bank size is an important and consistent determinant of risk whereas diversification is not. Our results inform the continuing debate on diversification versus functional separation of bank activities.